Evolutionary study and phylodynamic pattern of human influenza A/H3N2 virus in Indonesia from 2008 to 2010. - Agustiningsih Agustiningsih; Hidayat Trimarsanto; Restuadi Restuadi; I Made Artika; Margaret Hellard; David Handojo Muljono (PLoS ONE)
Influenza viruses are by nature unstable with high levels of mutations. The sequential accumulation of mutations in the surface glycoproteins allows the virus to evade the neutralizing antibodies. The consideration of the tropics as the influenza reservoir where viral genetic and antigenic diversity are continually generated and reintroduced into temperate countries makes the study of influenza virus evolution in Indonesia essential. A total of 100 complete coding sequences (CDS) of Hemagglutinin (HA) and Neuraminidase (NA) genes of H3N2 virus were obtained from archived samples of Influenza-Like Illness (ILI) surveillance collected from 2008 to 2010. Our evolutionary and phylogenetic analyses provide insight into the dynamic changes of Indonesian H3N2 virus from 2008 to 2010. Obvious antigenic drift with typical 'ladder-like' phylogeny was observed with multiple lineages found in each year, suggesting co-circulation of H3N2 strains at different time periods. The mutational pattern of the Indonesian H3N2 virus was not geographically related as relatively low levels of mutations with similar pattern of relative genetic diversity were observed in various geographical origins. This study reaffirms that the existence of a particular lineage is most likely the result of adaptation or competitive exclusion among different host populations and combination of stochastic ecological factors, rather than its geographical origin alone.